2010
DOI: 10.1111/j.1439-0388.2008.00789.x
|View full text |Cite
|
Sign up to set email alerts
|

Different models for evaluation of growth traits and Kleiber ratio in an experimental flock of Iranian fat‐tailed Afshari sheep

Abstract: Records for Afshari sheep were retrieved from data collected between 2000 and 2005 at the Zanjan University experimental flock, at Zanjan, Iran. (Co)variance components and corresponding genetic parameters for birth weight (BW), weaning weight (WW), 6-month weight (W6), average daily gain from birth to weaning (ADGa), from birth to 6 months (ADGb), from weaning to 6 months (ADGc), Kleiber ratio at weaning (WWKR) and Kleiber ratio at 6 months of age (W6KR) were estimated using univariate and bivariate analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
28
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 20 publications
12
28
3
Order By: Relevance
“…Among traits studied, BW had the minimum CV. Miraei-Ashtiani et al (2007) in Sangsari sheep and Eskandarinasab et al (2010) in Afshari sheep reported similar findings. The reason of less CV for BW may be due to less variation and effect of outside environment on this trait, as ewes were kept inside and manually fed in the late months of pregnancy period in the winter (MiraeiAshtiani et al 2007).…”
Section: Resultssupporting
confidence: 76%
“…Among traits studied, BW had the minimum CV. Miraei-Ashtiani et al (2007) in Sangsari sheep and Eskandarinasab et al (2010) in Afshari sheep reported similar findings. The reason of less CV for BW may be due to less variation and effect of outside environment on this trait, as ewes were kept inside and manually fed in the late months of pregnancy period in the winter (MiraeiAshtiani et al 2007).…”
Section: Resultssupporting
confidence: 76%
“…In relation to ADG1, heritability values reported in the literature range from 0.11 to 0.22 (ABEGAZ et al, 2005;ESKANDARINASAB et al, 2010;GHAFOURI-KESBI et al, 2011), higher than those found in this paper. For ADG2, the estimate was in range with fi ndings of ESKANDARINASAB et al (2010) were similar to the results presented.…”
Section: Resultscontrasting
confidence: 53%
“…The heritability estimates for average daily gains during (birth-3 months), (3-6 months) and (6-12 months) periods were 0.20±0.06, 0.24±0.07 and 0.17±0.06 and the corresponding Kleiber ratios were 0.25±0.07, 0.23±0.06 and 0.17±0.06, respectively. The heritability estimates of pre weaning growth rates were within the range of literature (Eskandarinasab et al, 2011;Mohammadi et al, 2011;Prakash et al, 2012;Savar-Sofla et al, 2011;Mokhtari et al, 2012 andKesbi, 2013). Literature suggested that heritability estimates for post weaning growth rates of various sheep breeds had wider range where the estimates ranged from 0.02 in Moghani sheep (Savar-Sofla et al, 2011) to 0.70 in Menz sheep (Gizaw and Jushi 2004).…”
Section: Genetic Parameterssupporting
confidence: 56%